ANDROID-BASED DEVELOPMENT OF INTERACTIVE MULTIMEDIA LEARNING APPLICATION SYSTEMS FOR CHILDREN - Krisno, Reynaldo; Rarasati, Dionisia Bhisetya (Jurnal Algoritma, Logika dan Komputasi, 2023)
Technological developments have progressed very rapidly, marked by progress in the field of technology and information. Information technology has now spread to almost all aspects of life, one of which is that it has entered the educational aspect which is used as an interesting learning medium, because it is able to provide new colors in the learning process, and can use a learning while playing approach so that the learning process can feel happy, so that later students are able to express themselves maximally in the learning process. In education there are many things that need to be considered in child development so as to avoid various obstacles in the learning process, such as color blindness, speech delays, and other pre-school abilities by introducing cognitive education to children such as recognition of numbers, letters, colors. And according to IDAI this cognitive recognition period is recommended for children aged 2 -5 years. Researchers developed an Android-based interactive multimedia learning system for children with the aim of providing facilities to parents for children in introducing cognitive aspects with new colors, namely in the form of interactive multimedia applications. The development method used is MDLC (Multimedia Development Life Cycle), because the application being developed involves various media such as sound, images and text. The development of this application also applies quiz content to maximize children's learning media. Through testing using Black Box Testing, the WARUKA Education application that was developed managed to achieve good results. All the features contained in the application run well and as expected. In the User Acceptance Testing test using a questionnaire, the WARUKA Education application gets positive results, with a user satisfaction percentage of 94.167%. Based on this percentage, the WARUKA Education application can be categorized as very good, indicating very high acceptability for users.